Persistent and occasional poverty and children's food consumption: evidence from a longitudinal Québec birth cohort. Issue 10 (26th June 2014) - Kakinami, Lisa; Gauvin, Lise; Séguin, Louise; Lambert, Marie; Nikiema, Béatrice; Paradis, Gilles
Abstract : Background: Childhood poverty is associated with poorer food consumption but longitudinal data are limited. The objective was to assess if food consumption differs depending on age (6, 7, 10 and 12 years) and pattern of poverty. Methods: Participants were from the 1998–2010 'Quebec Longitudinal Study of Child Development' birth cohort. Poverty was defined as income below the low-income thresholds established by Statistics Canada which adjusts for household size and geographic region. Multiple imputation was used for missing data, and latent class growth analysis identified poverty trajectories. Multivariable ordinal logistic regression assessed the association between poverty and greater consumption of milk, cheese, fruits, vegetables, sweets and sugar-sweetened beverages (SSB). Results: Four poverty trajectories were identified: 1 reference category (stable non-poor) and 3 higher-risk categories (stable poor, increasing and decreasing risk). The probability of more frequent consumption was lower among children from stable poor households compared to children from stable non-poor households for fruit (6, 10 and 12 years), milk and vegetables (6, 7, 10 and 12 years) but was higher for SSB (10 and 12 years). Among children from increasing and decreasing poverty households compared to stable non-poor households, the probability of greater consumption of fruits and vegetables was lower and greater consumption of SSB was higher by the age of 12 years. Conclusions: While experiencing continual exposure to poverty has detrimental effects on food consumption throughout childhood, the association for milk, fruits and vegetables does not differ across age. Intermittent exposure to poverty may also have long-lasting effects.